Implementasi Praktikum Biologi Berbasis Teknologi untuk Peningkatan Kompetensi Siswa dan Guru di SMU N 15 Padang - Rita Maliza; Muhammad Idris; Ashrifurrahman Ashrifurrahman; Arthauly Yopita Sinurat; M.Nazri Janra; Nofrita Nofrita; Muhammad Syukri Fadil; Robby Jannatan; Mansyurdin Mansyurdin; Wilson Novarino; Kurniadi Ilham; Putra Santoso; Henny Herwina; Bramadi Arya; Tasya Putri Pratama Elisa; Reziq Marchellino Irwan (Buletin Dharmas Andalas, 2026)
This community service activity was conducted on October 27, 2025, at SMA Negeri 15 Padang, with the aim of enhancing the competencies of teachers and students in biotechnology through the integration of modern technology as part of the digital transformation of education. The methods employed included direct training and mentoring, supported by a guidebook entitled “Basic Biology and Biotechnology: From Microscope to DNA.” The activity was organized into several thematic groups, namely plant and animal tissue histology, animal anatomy, plant culture, and DNA isolation. The results demonstrated a significant improvement in participants’ abilities to operate basic biotechnology tools, understand applied biotechnology concepts, and develop innovative practicum activities aligned with the Merdeka Curriculum. In addition, this activity strengthened collaboration among schools, universities, and media in disseminating science learning innovations. In conclusion, the implementation of technology-based biology practicum is effective in improving participants’ competencies and scientific literacy and has strong potential for sustainable development through continued mentoring and the development of digital modules.